On the concepts of balls in a D-metric space - S. V. R. Naidu; K. P. R. Rao; N. Srinivasa Rao (International Journal of Mathematics and Mathematical Sciences)
The various concepts of open balls in D-metric spaces are studied in the case of certain D-metric spaces and many results in the literature on such balls are shown to be false.